(untitled) (Journal of EAHIL, 2017)
KnowledgeShare, a web-based application, was produced to manage core services (evidence searching, teaching, current awareness), to increase access to evidence, and to aid collaborative working. The system enables library and knowledge service (LKS) staff to collaborate on and deliver personalised, targeted updates to members about healthcare topics in their field. Through KnowledgeShare, members can connect with one another based on shared professional interests. KnowledgeShare has been implemented at Brighton and Sussex NHS Library and Knowledge Service and extended to other LKS teams in the South East of England. The system has enabled the creation of an extended network of LKS teams who can standardise quality, spread the workload of current awareness provision and share evidence reviews.